Comparison of Peritonsillar Bupivacaine versus Peritonsillar Dexamethasone in Post-Tonsillectomy Pain Management - Najeebullah Khan, Mirza Khizar Hameed, Iftikhar Aslam, Irshad Ali, Amir Akbar, Nudrat Khalil (Journal of Rawalpindi Medical College, 2021)
Objective: To compare efficacy of Peritonsillar Dexamethasone with Peritonsillar Bupivacaine in managing post-tonsillectomy pain in children. Study design: Randomized Controlled Trial Setting & Period: ENT Department Fauji Foundation Hospital (FFH) Rawalpindi from 01-06-2019 to 31-11-2020. Material &Methods: A total of sixty patients of both genders between ages of 5-15 years fulfilling the recognized criteria for tonsillectomy were selected. They were equally divided into two groups; Group A received peritonsillar Bupivacaine while Group B received peritonsillar Dexamethasone. Mean post-tonsillectomy Visual Analogue Score (VAS) at 1st, 2nd and 7th day were recorded in both groups and compared using independent sample ‘t’ test. Results: In group A Mean post-tonsillectomy VAS at 24 hours was 6.73±1.44 SD while in group B it was 5.93±1.26 SD (p-value 0.025). Mean post-tonsillectomy VAS at 48 hours was 5.60±1.25 SD and 4.37±1.03 SD (p-value 0.000) respectively in groups A and B. At 7th post operative day, Mean VAS was noted as 3.27±0.74 SD and 2.30±0.79 SD (p-value 0.000) respectively in group A and B. Conclusion: Peritonsillar Dexamethasone is more effective than peritonsillar Bupivacaine in controlling post-tonsillectomy pain in children. Statistically significant difference was noted for mean post-tonsillectomy VAS at 1st, 2nd and 7th day. Key Words: Tonsillectomy, visual analogue score, postoperative pain, dexamethasone, bupivacaine.